Seed- and leaf-based expression of FGF21-transferrin fusion proteins for oral delivery and treatment of non-alcoholic steatohepatitis - Hou, Hsuan-Wu; Bishop, Christopher A.; Huckauf, Jana; Broer, Inge; Klaus, Susanne; Nausch, Henrik; Buyel, Johannes F. (Frontiers in Plant Science, 2022)
Non-alcoholic steatohepatitis (NASH) is a global disease with no effective medication. The fibroblast growth factor 21 (FGF21) can reverse this liver dysfunction, but requires targeted delivery to the liver, which can be achieved via oral administration. Therefore, we fused FGF21 to transferrin (Tf) via a furin cleavage site (F), to promote uptake from the intestine into the portal vein, yielding FGF21-F-Tf, and established its production in both seeds and leaves of commercial N. tabacum cultivars, compared their expression profile and tested the bioavailability and bioactivity in feeding studies. Since biopharmaceuticals need to be produced in a contained environment, e.g. greenhouses in case of plant, the seed production was increased in this setting from 239 to 380 g m-2 a-1 seed mass with costs of 1.64 € g-1 by side branch induction, whereas leaves yielded 8,193 g m-2 a-1 leave mass at 0.19 € g-1. FGF21-F-Tf expression in transgenic seeds and leaves yielded 6.7 and 5.6 mg kg-1 intact fusion protein, but also 4.5 and 2.3 mg kg-1 additional Tf degradation products. Removing the furin site and introducing the liver-targeting peptide PLUS doubled accumulation of intact FGF21-transferrin fusion protein when transiently expressed in N. benthamiana from 0.8 to 1.6 mg kg-1, whereas truncation of transferrin (nTf338) and reversing the order of FGF21 and nTf338 increased the accumulation to 2.1 mg kg-1 and decreased the degradation products to 7%. Application of partially purified nTf338-FGF21-PLUS to FGF21-/- mice by oral gavage proved its transfer from the intestine into the circulation and acutely affected hepatic mRNA expression. Hence, the medication of NASH via oral delivery of nTf338-FGF21-PLUS containing plants seems possible.